Efficacy and safety of mirabegron, a β3‐adrenoceptor agonist, in patients with detrusor hyperactivity and impaired contractility. Issue 2 (26th April 2018) - Lee, Cheng‐Ling; Kuo, Hann‐Chorng
Abstract : Objective: We examined the efficacy and safety of mirabegron in elderly patients with urodynamic detrusor hyperactivity with impaired contractility (DHIC). Methods: Patients diagnosed with DHIC received daily dose of mirabegron (25mg). Subjective symptom scores, uroflowmetry data, and adverse events (AEs) were recorded for all patients at baseline and after 1, 3, and 6 months treatment. Comparisons were made for each patient individually and between patients with detrusor overactivity (DO). Results: Of the 65 patients enrolled in the study, 25 had DHIC and 40 had DO (mean [± SD] age 79.3 ± 9.6 and 75.6 ± 10.7 years, respectively). At the 6‐month follow‐up, significant ( P  < .05) improvement was seen compared with baseline in both the DHIC and DO groups in terms of OAB symptom scores (4.72 ± 3.05 vs. 6.88 ± 4.06 and 4.50 ± 2.99 vs. 6.70 ± 3.60, respectively), urgency severity score (1.90 ± 2.00 vs. 3.35 ± 1.13 and 1.58 ± 1.93 vs. 3.00 ± 1.65, respectively), and global response assessment (1.80 ± 1.41 and 1.73 ± 1.34, respectively). In the DHIC group, post‐void residual (PVR) volume decreased from 153 ± 52.7 mL at baseline to 85.8 ± 90.1 mL at 6th month ( P  < .05) and voiding efficiency improved from 40.0 ± 20.7% to 62.6 ± 28.3% ( P  < .05). Common AEs included dry mouth and dizziness, yet 16% of DHIC patients developed PVR >180 mL. Conclusion: Mirabegron was an effective treatment option in elderly patients with urodynamic DO and DHIC in the present study. The AEs reported were mild and infrequent.